FORECASTING OF COLOURS IN CREATIVE COMPOSITION OF TEXTILE FABRIC AND FASHION - Ghosh, Reeta (International Journal of Research -GRANTHAALAYAH, 2014)
Colour is the most enriched and endless form of human life. It reflects our mood and more importantly, it has more influence and effect on our lives than we realize. How can we define colour, a reality, a feeling that creates energy, enthusiasm, potential, anger, affection, passion and many other feelings in us. If we are in pleasant feeling, colour fills us with the feel of joy and happiness and in contrary to this if we are unhappy and sad the colours are there, who fill with the feel of unhealthy, unhappiness and sadness. Now it is a matter to think upon that why we correlate our feelings with colour or how colour reflects our mood or our internal expressions in a physical manner. It is not only because of colour but of course because of its composition too. We always look for a new colour palette range or a new invention but have we ever thought that from where did colours come and why they show their impact on us and our lives. Craving for colour, forces human to create invent and generate inventions, of course a human with artistic or creative brain and heart, who not only evolve in engraving of colours but also put efforts in to it to foster.